(untitled) (Global Journal of Medical Research, 2013)
India being an emerging economy, it concentrates maximum resources towards indigenization of various technologies making them economically viable to the general population. Presently roughly half of the country dwells in villages and small towns where even basic sanitation and primary health-care facilities are virtually non-existent. Deteriorating environmental conditions have lead to increased susceptibility to various respiratory diseases prompting an early diagnosis from preventive health considerations. All these factors contribute to a product development philosophy which addresses cost considerations more profoundly in addition to technical accuracy. This paper demonstrates the development of a low cost, portable Spirometer for application in rural health-care centres across India. First proto-type of a Computer based Spirometer system has been realized employing a solidstate pressure sensor based approach. A dedicated analog signal acquisition and processing channel was designed and tested in tandem with the solid-state pressure sensor. Calibration of the pressure sensor for known values of applied pressure was performed for linearity tests. The 8051 core was employed in designing the micro-controller firmware program for digitization and transmission of the signal to the computer. Dedicated computer software for data acquisition, display and analysis was developed in Lab-windows platform.